2018 IEEE/PES Transmission and Distribution Conference and Exposition (T&D) 2018
DOI: 10.1109/tdc.2018.8440391
|View full text |Cite
|
Sign up to set email alerts
|

Data Fusion and Machine Learning Integration for Transformer Loss of Life Estimation

Abstract: Rapid growth of machine learning methodologies and their applications offer new opportunity for improved transformer asset management. Accordingly, power system operators are currently looking for data-driven methods to make better-informed decisions in terms of network management. In this paper, machine learning and data fusion techniques are integrated to estimate transformer loss of life. Using IEEE Std. C57.91-2011, a data synthesis process is proposed based on hourly transformer loading and ambient temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Hourly generation of dispatchable DGs is constrained by the maximum and minimum capacity limits (15), where the unit commitment state variable I would be 1 when the unit is committed and 0 otherwise. Constraints (16)- (19) represent ramp up and ramp down constraints of dispatchable DG units, where (16) and (18) belong to intra-day intervals and (17) and (19) represent ramping constraints for inter-day intervals. Dispatchable DG units are subject to the minimum up and down time limits, represented by (20)- (23).…”
Section: Paper Contributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hourly generation of dispatchable DGs is constrained by the maximum and minimum capacity limits (15), where the unit commitment state variable I would be 1 when the unit is committed and 0 otherwise. Constraints (16)- (19) represent ramp up and ramp down constraints of dispatchable DG units, where (16) and (18) belong to intra-day intervals and (17) and (19) represent ramping constraints for inter-day intervals. Dispatchable DG units are subject to the minimum up and down time limits, represented by (20)- (23).…”
Section: Paper Contributionmentioning
confidence: 99%
“…A fuzzy modelling in [14] is applied for transformer asset management while improvement in the remaining life of a transformer is achieved by a fuzzy model system. Application of different machine learning methods, such as Adaptive Network-Based Fuzzy Inference System (ANFIS), Multi-Layer Perceptron (MLP) network and Radial Basis Function (RBF) network, in estimating transformer loss of life is presented in [15], where further these methods are fused together to improve the estimation accuracy [16]. In [17], an artificial neural network is modelled to predict top oil temperature in a transformer, where ambient temperature and load current are considered as the input layer and top oil temperature as the output layer.…”
mentioning
confidence: 99%
“…T. H. Loutas et al [6] reported a data-driven approach for the remaining useful life estimation of rolling element bearings based on -Support Vector Regression. In another paper [7], L. L. Li et al [8] presented a general data-driven, similarity-based approach for residual useful life estimation for industrial components or systems.…”
Section: Introductionmentioning
confidence: 99%